2014
DOI: 10.3389/fchem.2014.00065
|View full text |Cite
|
Sign up to set email alerts
|

Development of ricehusk ash reinforced bismaleimide toughened epoxy nanocomposites

Abstract: Recent past decades have witnessed remarkable advances in composites with potential applications in biomedical devices, aerospace, textiles, civil engineering, energy, electronic engineering, and household products. Thermoset polymer composites have further enhanced and broadened the area of applications of composites. In the present work epoxy-BMI toughened-silica hybrid (RHA/DGEBA-BMI) was prepared using bismaleimide as toughener, bisphenol-A as matrix and a silica precursor derived from rice husk ash as rei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 40 publications
1
16
0
Order By: Relevance
“…Since RHAs are richer in carbon content, in particular the RHA-MG, the thermograms of the composites prepared with different amounts of RHAs presented higher mass loss when compared with those prepared with silica. Previous studies that analyzed epoxy composites prepared with small amounts of RHA (of up to 5%) reported similar degradation behavior as that observed in the present work, also at one stage only and at temperature above 300 ºC 30,31 . For the authors of these works, such behavior indicates the absence of volatiles such as water or solvents.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Since RHAs are richer in carbon content, in particular the RHA-MG, the thermograms of the composites prepared with different amounts of RHAs presented higher mass loss when compared with those prepared with silica. Previous studies that analyzed epoxy composites prepared with small amounts of RHA (of up to 5%) reported similar degradation behavior as that observed in the present work, also at one stage only and at temperature above 300 ºC 30,31 . For the authors of these works, such behavior indicates the absence of volatiles such as water or solvents.…”
Section: Resultssupporting
confidence: 89%
“…In a study that evaluated the effect of smaller filler proportions (0.5%, 1%, and 1.5%) the authors also observed that water absorption drops with increasing filler amounts, explaining that this may be due to the inherent hydrophobic nature of the crosslinking formed when silica is added and during the epoxy curing reaction 31 . Poor water absorption is a very important characteristic in various epoxy applications.…”
Section: Resultsmentioning
confidence: 99%
“…However, there were slightly decreased strain values from 30.7% at 30 rpm to 30.37% at 40 rpm and 29.9% at 50 rpm. The modulus decreased from 48 MPa to 22 MPa at 30 rpm and 40 rpm, respectively, but increased at 50 rpm to 76 MPa, which showed a good dispersion of fiber in the polymer matrix (Kanimozhi et al 2014). The maximum tensile strength was 10.62 MPa observed at the rotational velocity of 40 rpm, as reported previously (El-Shekeil et al 2011); therefore, it was taken as the optimum velocity in further synthesis reactions.…”
Section: Effect Of Change In Rotational Velocitymentioning
confidence: 56%
“…Figure 7 depicts the FT-IR spectra of the neat TPU and different sizes of the sugar palm fiber (SPF), reinforced with the TPU system, which showed identical behavior just like the neat TPU, i.e. identical peaks but with low intensity (Kanimozhi et al 2014). This result was attributed to the fact that the untreated fiber is grafted on the polymer surface by physical interactions such as hydrogen bonding which resulted in the low-intensity C=O peaks.…”
Section: Impact Strength Study At Different Fiber Sizesmentioning
confidence: 72%
See 1 more Smart Citation